Life‐Space Mobility and Parkinson's Disease. A Multiple‐Methods Study. Issue 3 (19th January 2022) - Ryder‐Burbidge, Charlotte; Wieler, Marguerite; Nykiforuk, Candace I.J.; Jones, C. Allyson
ABSTRACT: Background: Life‐space mobility (LSM) captures a broad spectrum of mobility in physical and social environments; however, it has not been extensively studied in Parkinson's disease. Using a multiple‐methods approach, individual, social and environmental factors that impact LSM were explored in PD. Methods: Two hundred twenty‐seven participants with PD (n = 113) and a comparative group without PD (n = 114) were recruited from the community. Within a cross‐sectional survey, LSM (University of Alabama Birmingham Life‐Space Assessment, LSA) was compared in the two groups. Using multiple linear regression, socio‐demographics, lifestyle behaviors, medical, mobility and social factors were examined to identify factors that explained LSM. A qualitative narrative inquiry was completed to augment the findings from the survey; 10 participants with PD were interviewed regarding facilitators and barriers to mobility. Results: The mean overall LSA‐composite score for the PD group was 64.2 (SD = 25.8) and 70.3 (SD = 23.1) for the community comparative group (mean difference = 6 points, 95%CI:‐0.4, 12.5) indicating most participants moved independently beyond their neighborhoods. A higher proportion of the PD group required assistance with mobility than the community comparison group. Not driving, receiving caregiving, lower social participation, and lower monthly family finances were associated with restricted LSM in the PD group. Data from qualitative interviews supported quantitative findings and offered insights into the features of the built environment that facilitate and restrict mobility. Conclusion: Individual, social and environmental factors are associated with the LSM among persons with PD. Clinicians and policy‐makers should include both individual and community‐based factors when developing interventions to encourage the LSM of the PD population.